Farnesoid X Receptor and Its Ligands Inhibit the Function of Platelets. Issue 12 (December 2016) - Moraes, Leonardo A.; Unsworth, Amanda J.; Vaiyapuri, Sakthivel; Ali, Marfoua S.; Sasikumar, Parvathy; Sage, Tanya; Flora, Gagan D.; Bye, Alex P.; Kriek, Neline; Dorchies, Emilie; Molendi-Coste, Olivier; Dombrowicz, David; et al.
Abstract : Objective—: Although initially seemingly paradoxical because of the lack of nucleus, platelets possess many transcription factors that regulate their function through DNA-independent mechanisms. These include the farnesoid X receptor (FXR), a member of the superfamily of ligand-activated transcription factors, that has been identified as a bile acid receptor. In this study, we show that FXR is present in human platelets and FXR ligands, GW4064 and 6α-ethyl-chenodeoxycholic acid, modulate platelet activation nongenomically. Approach and Results—: FXR ligands inhibited the activation of platelets in response to stimulation of collagen or thrombin receptors, resulting in diminished intracellular calcium mobilization, secretion, fibrinogen binding, and aggregation. Exposure to FXR ligands also reduced integrin αIIb β3 outside-in signaling and thereby reduced the ability of platelets to spread and to stimulate clot retraction. FXR function in platelets was found to be associated with the modulation of cyclic guanosine monophosphate levels in platelets and associated downstream inhibitory signaling. Platelets from FXR-deficient mice were refractory to the actions of FXR agonists on platelet function and cyclic nucleotide signaling, firmly linking the nongenomic actions of these ligands to the FXR. Conclusions—: This study provides support for the ability of FXR ligands to modulate platelet activation. The atheroprotective effects of GW4064, with its novel antiplatelet effects, indicate FXR as a potential target for the prevention of atherothrombotic disease. Abstract : Supplemental Digital Content is available in the text.